A chat with Dr. Birama Sidibe, Founder of Agrobiotech, Mali (Episode 4) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this episode, Dr Sidibe talks about Agrobiotech's partnership with the Islamic Development Bank for Guinea food system.